Morphological and taxonomic study of eggs of some fish families with a reference to their abundance in the North West of Arabian Gulf - Al-Okailee, M.T.K. (Mesopotamian Journal of Marine Sciences, 2022)
Sampling of eggs of fish was conducted at two stations in the northwestern part of Arabian Gulf (Shatt Al-Arab estuary (A1) and Khor Amaya (A2)), during April 2012 to March 2013. A total of 2902 fish eggs were collected using conical plankton net (mesh size 330µm). Six families (Sciaenidae, Clupeidae, Soleidae, Polynemidae, Engraulidae and Ariidae) of fish eggs were identified. Sciaenid fish egg comprised 45.6 % of all eggs collected and peak of abundance (1680.3 egg/10m²) at station A2 was occurred in May. Water temperature was ranged from 13-34ºC and salinity was 32-42 ‰. Water temperature seems to be the most vital factor in determining the onset of the spawning of fish in the Arabian Gulf. This study showed the importance of the northwestern part of the Arabian Gulf as a spawning and nursery site for the Sciaenidae, Clupeidae, Soleidae, Polynemidae, Engraulidae and the Ariidae.